The Gambaran Tingkat Distress Dan Faktor-Faktor Yang Memengaruhi Pada Perawat Di RSUD X Tembilahan Tahun 2022: Validasi Dan Reliabilitas Copenhagen Psychosocial Questionnaire Version III: The Description And Factors Associated With Distress Level Among Nurse In RSUD X Tembilahan Year 2022: Validation And Reliability Of Copenhagen Psychosocial Questionnaire Version III - Yussy Rha, Warda; Tejamaya, Mila (Promotif : Jurnal Kesehatan Masyarakat, 2022)
Nursing is one of the stressful professions. Stress emerged on nurses due to various factors, They have affected nurses in the form of tiredness, harsh behavior, anxiety, increase of blood pressure, lack of self-confidence, lack of job satisfaction, decrease in efficiency, etc. The Copenhagen Psychosocial Questionnaire (COPSOQ) is one of a few research-based instruments that have been developed for use at workplaces as well as for research purposes. The instrument is internationally recognized as a risk assessment tool by both the International Labour Organization and the World Health Organization and is used in workplace surveys worldwide for work environment development and follow-up of organizational changes. This study aims to analyze the validity and reliability of the Copenhagen Psychosocial Questionnaire (COPSOQ III) on Nurse at RSUD X. The study design is cross-sectional. Determination of the sample of this study using simple random sampling method of Nurse in RSUD X, The questionnaire was based on COPSOQ III scales, Validity and Reliability tests using Pearson Product Moment and Cronbach's alpha.